Metacognitive Strategies in Learning Speaking Skills in The 60-Hari Lancar Berbahasa Arab - Urrahmah, Nisa’; Rizky Yani, Pobry; Mawaddah Opier, Ulfa (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2023)
In overcoming difficulties communicating in Arabic, students apply learning strategies as an effort to facilitate learning. A learning strategy is defined as a series of steps taken to achieve learning goals, helping students have more fun and understand the material more easily. The "60 Days of Fluent Arabic" program is a solution with implementation for two months, divided into three levels using the book Al-Arabiyyah Baina Yadaik.This research uses observation and interviews as data collection techniques at the Darul Lughah Banda Aceh Course. In this program, participants are taught to speak Arabic correctly using the direct method, where the teacher uses Arabic as the language of instruction. Metacognitive strategies focus on the learning process, organizing, planning and evaluating to increase participants' self-confidence. The process focus stage involves connecting to previous knowledge and delaying speaking to focus on listening.The stages of organizing and planning learning play an important role, with agreements between teachers and participants, writing notes, and creating an Arabic language environment. Evaluations are carried out daily and at the end of the semester to measure participant progress. للتغلب على صعوبات التواصل باللغة العربية، يطبق الطلاب استراتيجيات التعلم كمحاولة لتسهيل التعلم. يتم تعريف استراتيجية التعلم على أنها سلسلة من الخطوات التي يتم اتخاذها لتحقيق أهداف التعلم، مما يساعد الطلاب على الحصول على مزيد من المتعة وفهم المواد بسهولة أكبر. برنامج "60 يوم من اللغة العربية بطلاقة" حل مع التنفيذ لمدة شهرين مقسم إلى ثلاثة مستويات باستخدام كتاب العربية بينة يديك.يستخدم هذا البحث الملاحظة والمقابلات كتقنيات لجمع البيانات في دورة دار اللغة باندا آتشيه. يتم في هذا البرنامج تعليم المشاركين التحدث باللغة العربية بشكل صحيح باستخدام الطريقة المباشرة، حيث يستخدم المعلم اللغة العربية كلغة التدريس. تركز استراتيجيات ما وراء المعرفية على عملية التعلم والتنظيم والتخطيط والتقييم لزيادة ثقة المشاركين بأنفسهم. تتضمن مرحلة التركيز على العملية الاتصال بالمعرفة السابقة وتأخير التحدث للتركيز على الاستماع.تلعب مراحل تنظيم وتخطيط التعلم دورًا مهمًا، مع الاتفاق بين المعلمين والمشاركين، وكتابة الملاحظات، وتهيئة بيئة اللغة العربية. يتم إجراء التقييمات يوميًا وفي نهاية الفصل الدراسي لقياس مدى تقدم المشاركين.